PERSEPSI DAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN INFRASTRUKTUR (STUDI KASUS PEMBANGUNAN MRT RUTE KORIDOR SELATAN-UTARA, TAHAP 1, LEBAK BULUS JAKARTA SELATAN - Atried Kharisma; Edi Santosa; Puji Astuti (Journal of Politic and Government Studies, 2017)
Infrastructure development is an important part of an expansion of a regionand country which is the duties and obligations of the center or local government. Ininfrastructure development social aspects should be noticed in order to realize a participatoryand quality development. MRT (Mass Rapid Transit) development policy is a policy to increasethe infrastructure development. This research was a development study which reviewed on howthe perception and participation of the society towards the infrastructure developmentparticularly in MRT (Mass Rapid Transit) development in Lebak Bulus District, South Jakarta.This was a mixed research method between quantitative and qualitative with samplingtechnique using questionnaire, interview and document. The main focuses in this research werethe context of society perception to MRT (Mass Rapid Transit) development in Lebak BulusDistrict, South Jakarta, society participation towards the MRT (Mass Rapid Transit)development in Lebak Bulus District, South Jakarta, and the correlation of perception andparticipation of the society towards the MRT (Mass Rapid Transit) development in Lebak BulusDistrict, South Jakarta from its implementation in the field.Keywords : Infrustructure Development, Perception, Participation